Car ownership and commuting mode of the “original” residents in a high-density city center: A case study in Shanghai - Tao Chen; Haixiao Pan; Yanbo Ge (Journal of Transport and Land Use)
As a result of rapid urbanization and motorization in China, numerous mega-cities have emerged, and large numbers of people live and work in the city centers. Consequently, developing a public transport-oriented urban structure and promoting sustainable development are major planning strategies for the country. To understand the impact of rail transit on motorization in a high-density city center, we conduct a household travel survey in three neighborhoods around metro stations in the central area of Shanghai. We examine the car buying and commuting behavior of those Shanghai “original” residents who lived there when the city began growing, engulfing them in the center.